Comparative genomics and proteomics of Eubacterium maltosivorans: functional identification of trimethylamine methyltransferases and bacterial microcompartments in a human intestinal bacterium with a versatile lifestyle - Feng, Yuan (2022)
Summary Eubacterium maltosivorans YIT is a human intestinal isolate capable of acetogenic, propionogenic and butyrogenic growth. Its 4.3-Mb genome sequence contains coding sequences for 4227 proteins, including 41 different methyltransferases. Comparative proteomics of strain YIT showed the WoodLjungdahl pathway proteins to be actively produced during homoacetogenic growth on H2 and CO2 while butyrogenic growth on a mixture of lactate and acetate significantly upregulated the production of proteins encoded by the recently identified lctABCDEF cluster and accessory proteins. Growth on H2 and CO2 unexpectedly induced the production of two related trimethylamine methyltransferases. Moreover, a set of 16 different trimethylamine methyltransferases together with proteins for bacterial microcompartments were produced during growth and deamination of the quaternary amines, betaine, carnitine and choline. Growth of strain YIT on 1,2-propanediol generated propionate with propanol and induced the formation of bacterial microcompartments that were also prominently visible in betaine-grown cells. The present study demonstrates that E. maltosivorans is highly versatile in converting low-energy fermentation end-products in the human gut into butyrate and propionate whilst being capable of preventing the formation of the undesired trimethylamine by converting betaine and other quaternary amines in bacterial microcompartments into acetate and butyrate.